Color vision disturbances secondary to oral tranexamic acid. Issue 3 (29th May 2021) - Kiser, Adam S.; Cooper, Gena L.; Napier, Jonathan D.; Howington, Gavin T.
Abstract: Tranexamic acid (TXA) is an antifibrinolytic commonly used to reduce blood loss due to surgical procedures, heavy menstruation, trauma, bleeding disorders, among other uses. Possible adverse reactions associated with TXA include abdominal pain, headache, fatigue, cerebral thrombosis, dizziness, retinal artery occlusion, chromatopsia, and more. We present a case of acute color vision disturbance developed soon after initiation of oral TXA for epistaxis prophylaxis in the setting of factor VII deficiency. To our knowledge we report the only case of color vision disturbance in a pediatric patient and the only case after receiving oral TXA. Soon after discontinuing oral TXA the patient's altered perception of color vision resolved. The patient was subsequently discharged home with a prescription for an alternative antifibrinolytic (aminocaproic acid) and follow‐up with neuro‐ophthalmology.